Efektivitas Projek Penguatan Profil Pelajar Pancasila Pada Mata Pelajaran Pendidikan Pancasila di SMK Swasta Kristen BNKP Gunungsitoli - Telaumbanua, Darisalim (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of the project, and analyze the types of activities of the Pancasila student profile strengthening project in the Pancasila education subject at the BNKP Gunungsitoli Christian Private Vocational School. This study uses a descriptive approach, qualitative method. The research instrument is the researcher himself, with data collection techniques in the form of observation, interviews and documentation. The results of the study and discussion concluded that: First, the Effectiveness of the Pancasila Student Profile Strengthening Project in the Pancasila Education subject at the BNKP Gunungsitoli Christian Private Vocational School has been carried out effectively, starting from the design, implementation, to evaluation and reflection stages, with the theme